Effects of pH dynamics on solidification/stabilization of municipal solid waste incineration fly ash. (1st February 2018) - Yakubu, Yahaya; Zhou, Jun; Ping, Duan; Shu, Zhu; Chen, Yun
Abstract: Fly ash (FA), a product of municipal solid waste incineration (MSWI), has been classified as a kind of hazardous waste due to its high content of heavy metals. FA may be reused in the construction industry or disposed of at landfill sites, and thus poses threats to both the environment and human health. This study sought to establish a scientific basis for accurate selection of suitable pH storage conditions for the FA. We evaluated the potential of MSWI FA sample from the Xinghuo waste incineration power plant, Wuhan, to solidify/stabilize the heavy metal (Cu, Pb, Zn, Cr, Cd, As and Mn) contents, when leached under different pH conditions. The concentration of a heavy metal in the leachate was assumed to inversely reflect the extent of its solidification/stabilization (S/S). The study findings showed that the raw FA contained higher levels of the heavy metals, which were above the acceptable limits. Extremely acidic conditions favoured heavy metal leaching compared to extremely alkaline conditions. The extent of S/S of heavy metals was generally very low under highly acidic conditions (pH ≤ 4), but increased with increasing pH. All the metals solidified/stabilized in pH media of 5–11, except Zn which was detected in the entire pH range. We conclude that changing landfill conditions which can affect the pH environment, will increase heavy metal leaching when the pH ≤ 4. As a result, waste which was initially classified as non-hazardous may later pose harmful risks to both humans and the environment alike. We propose pH of 5–11 as the optimum pH range for the treatment, reuse, and disposal of the ash sample. Highlights: The chemical and mineralogical composition of fly ash (FA) from the Xinghuo waste incineration power plant, Wuhan, China is presented. The FA is hazardous according to the USEPA 1311-TCLP regulatory guide due to high levels of Cu, Pb, Cr, Cd, and As. All the heavy metals studied leached in high acidic media (pH ≤ 4), and generally decreased with increasing pH. pH range of 5–11 is favourable for the treatment and disposal of FA. HCl produces results similar to that of HNO3 used in conventional leaching tests.